Géotechnique - Institution of Civil Engineers (Great Britain); Institution of Civil Engineers (Great Britain) (London; Institution of Civil Engineers, 1976)
"International journal of soil mechanics", Mar. 1959-
"International journal of soil mechanics", Mar. 1959-
English or French, with synopses in both 1950-
Pbk.
Keywords: Soil mechanics -- Periodicals; Engineering geology -- Periodicals